Application of q-Mittag-Leffer Function on Certain Subclasses of Analytic Functions - Jumaa, Abdulrahman Salman; al-Fayyad, Ali Hassan; Kassar, Osama Nazim (Iraqi Journal of Science, 2021)
The main objective of this paper is to introduce and study the generality differential operator involving the q-Mittag-Leffler function on certain subclasses of analytic functions. Also, we investigate the inclusion properties of these classes, by using the concept of subordination between analytic functions.